Effect of salinity and pH on selected immune functions of the Indian white shrimp, Fenneropenaeus indicus (H. Milne Edwards, 1837) - Sharma, Krupesha; Jayaprakash, Seema; Philipose, K K; Radhakrishnan, E V (Indian Journal of Fisheries, 2016)
The Indian white shrimp, Fenneropenaeus indicus, was subjected to environmental stresses like high (9) and low (5.5) water pH and decreasing water salinity (34 ‰ to 18 ‰) for a period of one week and certain vital immunological functions like total hemocyte count, total hemolymph protein and phenoloxidase activity were analysed to understand the effect of the environmental stress factors on these functions. The results indicated that while stress induced by change in the salinity had no damaging effects on the immune functions, stress caused by lower water pH induced more immunological damage when compared to higher water pH. Significantly decreased total hemocyte count and phenoloxidase activity were observed in shrimps exposed to lower pH when compared to shrimps exposed to higher pH and control shrimps. Also, lower pH significantly reduced the hemolymph protein values. It is therefore concluded that Fenneropenaeus indicus that are exposed to extreme pH show lowered immunological activity which would render the shrimp susceptible to infectious agents.